Nomenclatural Studies Toward a World List of Diptera Genus-Group Names. Part VIII: Hermann Loew - Evenhuis, Neal L.; Pape, Thomas; Ziegler, Joachim (Zootaxa, 2026)
The Diptera genus-group names of Hermann Loew are reviewed and annotated. A total of 404 available genus-group names in 64 families of Diptera are listed alphabetically for each name giving author, year and page of original publication, originally included species, type species and method of fixation, current status of the name, family placement, and a list of any emendations of it that have been found in the literature. Remarks are given to clarify nomenclatural or taxonomic information. Additionally, a full list of all species-group names proposed by Loew (3,762, of which 3,689 are available names) is presented with original date of publication and page number. An appendix gives a full bibliography of all scientific works published by Loew. Type species are designated for: Apedilia Loew, 1850e [Ceratopogonidae]; Eupedilia Loew, 1850e [Ceratopogonidae]; Tanyrrhina Bezzi, 1912 [Blephariceridae]. Corrected or clarified type-species, clarified type-species fixations and/or earlier dates of availability for nominal genera are given for the following genus-group names: Achalcus Loew, 1857c [Dolichopodidae]; Anarmostus Loew, 1860d [Asilidae]; Anorostoma Loew, 1862g [Heleomyzidae]; Antipalus Loew, 1849a [Asilidae]; Antiphrisson Loew, 1849a [Asilidae]; Apospasmica Loew, 1868e [Ulidiidae]; Ataracta Loew, 1850e [Limoniidae]; Bathypogon Loew, 1851d [Asilidae]; Centor Loew, 1864m [Chloropidae]; Coniceps Loew, 1873b [Richardiidae]; Echthistus Loew, 1849a [Asilidae]; Epiplatea Loew, 1868a [Richardiidae]; Epitriptus Loew, 1849a [Asilidae]; Eriopogon Loew, 1847f [Asilidae]; Eutolmus Loew, 1848b [Asilidae]; Euxesta Loew, 1868a [Ulidiidae]; Habropogon Loew, 1847f [Asilidae]; Hammatorrhina Loew, 1869i [Blephariceridae]; Holopogon Loew, 1847a [Asilidae]; Isopogon Loew, 1847f [Asilidae]; Lamprozona Loew, 1851d [Asilidae]; Laparus Loew, 1851d [Asilidae]; Lasiopogon Loew, 1847f [Asilidae]; Merosargus Loew, 1855c [Stratiomyidae]; Mochlonyx Loew, 1844b [Chaoboridae]; Mochtherus Loew, 1849a [Asilidae]; Nygmatodes Loew, 1845a [Psychodidae]; Proagonistes Loew, 1858c [Asilidae]; Pycnopogon Loew, 1847f [Asilidae]; Scoliocentra Loew, 1862e [Heleomyzidae]; Stictocephala Loew, 1873e [Ulidiidae]; Symmictus Loew, 1858c [Nemestrinidae]; Synarthrus Loew, 1857d [Dolichopodidae]; Tachista Loew, 1864r [Hybotidae]; Tephrochlamys Loew, 1862e [Heleomyzidae]; Teratopus Loew, 1858c [Asilidae]; Triptotricha Loew, 1872a [Xylophagidae]; Xanthochlorus Loew, 1857c [Dolichopodidae]. The following genus-group names previously treated as available have been found through research conducted in this work to be unavailable: Chaetostoma Loew, 1873e [Tephritidae]; Cryomobia Frey, 1913 [Heleomyzidae]; Spathidogaster Loew, 1876b [Syrphidae]; Tanyrhina Loew, 1862b [Blephariceridae]. Acting as First Reviser, the following correct original spellings for multiple original spellings are selected by us: Melanoloma Loew, 1873e [Richardiidae]; Platomodes Loew, 1855b [Bombyliidae]; Sphageus Loew, 1866e [Asilidae]. Also, acting as First Reviser, we select Antiphrisson sareptanus Lichtwardt, 1903 to have precedence over Antiphrisson thalhammeri Lichtwardt, 1903 as the valid name for the type species of Antiphrisson Loew, 1849 [Asilidae] and Synolcus tenuiventris Loew, 1858 to have precedence over Synolcus signatus Loew, 1858 as the valid name for the type species of Synolcus Loew, 1858. The following correct original spellings for multiple original spellings selected by First Reviser actions were missed by previous workers: Acidogona Loew, 1873b [Tephritidae]; Electra Loew, 1850e [Xylophagidae]; Empyelocera Loew, 1866h [Ulidiidae]; Tachista Loew, 1864g [Hybotidae]; Xanthochlorus Loew, 1857c [Dolichopodidae]. The following nominal genera are new junior synonyms of their respective senior synonyms: Acanthoneura Loew, 1862b of Acanthonevra Macquart, 1844, n. syn. [Tephritidae]; Apedilia Loew, 1850e of Serromyia Meigen, 1818, n. syn. [Ceratopogonidae]; Chrysochlamys Loew, 1858h of Ferdinandea Rondani, 1844, n. syn. [Syrphidae]; Clinorrhyncha Bertkau, 1893 of Ozirhincus Rondani, 1840, n. syn. [Cecidomyiidae]; Criorrhina Loew, 1871a of Criorhina Meigen, 1822, n. syn. [Syrphidae]; Dirrhiza Bertkau, 1893 of Dirhiza Loew, 1850c, n. syn. [Cecidomyiidae]; Eupedilia Loew, 1850e of Forcipomyia Meigen, 1818, n. syn. [Ceratopogonidae]; Exeretoneura Loew, 1860d of Exeretonevra Macquart, 1846, n. syn. [Xylophagidae]; Heligmoneura Loew, 1860d of Heligmonevra Bigot, 1858b, n. syn. [Asilidae]; Homalocephala Loew, 1873e of Setellia Robineau-Desvoidy, 1830, n. syn. [Richardiidae]; Leptomidas Loew, 1872a of Leptomydas Gerstaecker, 1868, n. syn. [Mydidae]; Loxoneura Loew, 1873e of Loxonevra Macquart, 1835, n. syn. [Platystomatidae]; Megarhina Loew, 1862b of Lynchiella Lahille, 1904, n. syn. [Culicidae]; Microdromia Loew, 1864h of Microdromya Bigot, 1857, n. syn. [Empididae]; Myia Loew, 1858c of Calliphora Robineau-Desvoidy, 1830, n. syn. [Calliphoridae]; Naeeta Loew, 1862b of Noeeta Robineau-Desvoidy, 1830, n. syn. [Tephritidae]; Nygmatodes Loew, 1845a of Nemopalpus Macquart, 1838a, n. syn. [Psychodidae]; Oncodocera Loew, 1862b of Ogcodocera Macquart, 1840, n. syn. [Bombyliidae]; Pachyrrhina Loew, 1871a of Nephrotoma Meigen, 1803. n. syn. [Tipulidae]; Phlebotomus Loew, 1845a, of Phlebotomus Rondani & Berté, 1840, n. syn. [Psychodidae]; Polistoides Loew, 1873e of Polystodes Robineau-Desvoidy, 1830, n. syn. [Platystomatidae]; Polydromia Loew, 1864h of Chelifera Macquart, 1823, n. syn. [Empididae]; Pterotaenia Rondani, 1868a of Apospasmica Loew, 1868e, n. syn. [Ulidiidae]; Ramphomyia Loew, 1840a of Rhamphomyia Meigen, 1822, n. syn. [Empididae]; Rhymosia Loew, 1872a of Rymosia Winnertz, 1864, n. syn. [Mycetophilidae]; Ryphus Loew, 1844a of Silvicola Harris, 1780, n. syn. [Anisopodidae]; Sitaria Loew, 1862b of Orellia Robineau-Desvoidy, 1830, n. syn. [Tephritidae]; Sympicnus Bigot, 1890 of Sympycnus Loew, 1857c, n. syn. [Dolichopodidae]; Tanyrrhina Bezzi, 1913 of Hammatorrhina Loew, 1869i, n. syn. [Blephariceridae]; Tephrochlamys Loew, 1862e of Heteromyza Fallén, 1820a, n. syn. [Heleomyzidae]; Toxoneura Loew, 1873e of Palloptera Fallén, 1810, n. syn. [Pallopteridae]; Xiphocerus Loew, 1847f of Xiphocera Macquart, 1834a, n. syn. [Asilidae]. Reversal of precedence is invoked for two cases of objective synonymy to promote stability in nomenclature: Aphrosylus Haliday in Walker, 1851b, nomen protectum and Aphrozylus Loew, 1850b, nomen oblitum [in Dolichopodidae]; Lynchiella Lahille, 1904, nomen protectum and Megarhina Loew, 1862b, nomen oblitum [in Culicidae].